HUBUNGAN SHIFT KERJA DENGAN KADAR HBA1C PASIEN DIABETES MELITUS TIPE II DI RUMAH SAKIT CAMATHA SAHIDYA KOTA BATAM - Mariaman Tjendera; Luis Yulia (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Work Shift and HbA1C Levels are part of health science, occupational safety, and internal medicine. The incidence of type II diabetes mellitus in Batam ranks lasts 10 most suffered. The number of type II diabetes mellitus patients at Camatha Sahidya Hospital was 1188 in 2014, and 315 in January to June. This research method was observational analytic with a cross-sectional approach conducted at Camatha Sahidya Hospital, Batam City. The sampling technique was accidental sampling with populations in November and December unknown, determining a minimum sample using the Lemeshow formula obtained a minimum sample of 97 people. The results of the study were analyzed by cross-tabulated frequency distribution and then tested by the Chi-square test. The results of this study found that type 2 HR patients with work shifts were 38 people (39.2%) while 59 people working in non-shift systems (60.8%). HbA1c laboratory examination results of DM patients with HbA1c> 8% more than the amount of HbA1c â‰¤8%, as many as 54 people (55.7%) type 2 DM patients with a total HbA1c> 8% and 43 people (44.3% ) Type 2 DM patients with HbA1c count â‰¤8%. There is a significant relationship between work shifts with HbA1c levels in type 2 DM patients at the Camatha Sahidya Hospital in Batam City in 2018 using the Chi-Square statistical test obtained p-value = 0.014 (p <0.05). Based on this study it can be concluded that there is a significant relationship between work shifts with HbA1C levels in type 2 DM patients at Camatha Sahidya Hospital, Batam City.